TWIP – TRIP effect in single crystalline VFeCoCrNi multi-principle element alloy. (15th March 2021) - Abuzaid, Wael; Egilmez, Mehmet; Chumlyakov, Yuri I.
Abstract: Various multi-principle element alloys exhibit superior mechanical properties across a wide range of temperatures including cryogenic temperatures. In most systems, the remarkable properties are attributed to deformation twinning (twinning induced plasticity). The recent VFeCoCrNi multi-principle element alloy displays a combined twinning induced plasticity effect, at room-temperature, and phase transformation at low deformation temperatures (transformation induced plasticity). This work considers single crystalline specimens of VFeCoCrNi loaded along the [111] direction. At room-temperature, slip dominates at low strains, below 22% plastic strain, and a delayed activation of twinning is observed. At 77 K, early activation of transformation, face-center cubic to body-center cubic having 111 F C C / / 110 B C C and 〈 110 〉 F C C / / 〈 111 〉 B C C parallel relations, was revealed. Graphical abstract: Image, graphical abstract